Multimedia the complete guide - Cooper, Brian (Dorling Kindersley, 1996)
This is an introduction to the cutting edge of technology for the general reader. It explains how the changes in information technology sweeping the world have come about, what they are, and how they will affect our lives in the future. CD-ROM technology, home shopping by television, the information superhighway, the creation of interactive games and virtual reality are all discussed, along with the benefits of multimedia. This is a guide for current consumers that can also inform newcomers to the technology. It features all the latest developments in hardware and software.